Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.peptides.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The apelinergic system in the developing lung: Expression and signaling

Abstract: a b s t r a c tApelin and its receptor APJ constitute a signaling pathway best recognized as an important regulator of cardiovascular homeostasis. This multifunctional peptidergic system is currently being described to be involved in embryonic events which extend into vascular, ocular and heart development. Additionally, it is highly expressed in pulmonary tissue. Therefore, the aim of this study was to investigate the role of apelinergic system during fetal lung development. Immunohistochemistry and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
14
1
2
Order By: Relevance
“…Many factors that regulate fetal lung branching morphogenesis activate signaling pathways that culminate with MAPK, PI3K/Akt and p38 cascades [30,31,40,41,42]. In the present study, ephrin-B1 was found not to modify the phosphorylated levels of these proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…Many factors that regulate fetal lung branching morphogenesis activate signaling pathways that culminate with MAPK, PI3K/Akt and p38 cascades [30,31,40,41,42]. In the present study, ephrin-B1 was found not to modify the phosphorylated levels of these proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, co-transfection of the AR and B1R in HUVECs results in increased eNOS activation in response to either apelin or the B1R ligand des-Arg 9 -BK, suggesting that this AR-B1R heteromer may be involved in the vasodilatory effects of apelin (Bai et al 2014). Beyond these studies showing heteromer formation, Piairo et al (2011) observed AR dimers and higher order oligomers in the developing lung using western blotting, but these multimers were not conclusively identified as being either homomeric or heteromeric in nature.…”
Section: Ar Dimerization/oligomerization and Its Impact On Cell Signamentioning
confidence: 87%
“…Then, the lungs were transferred to porous membranes (Isopore™ membrane filters, Merck Millipore, Germany) and cultured for 4 days as previously described [28,30]. The culture medium was replaced every 48 hours.…”
Section: Fetal Lung Explant Culturementioning
confidence: 99%